Impact of waste management on corporate sustainability: a case study of Nigerian breweries Plc (UNIZIK Journal of Marketing, 2024)
The issue of improper waste management has attracted global concerns as the inability to manage waste can lead to economic loss and environmental threats to human health and existence. Therefore, this study focused on waste management's effect on Nigerian Breweries Plc's corporate sustainability in Enugu State, Nigeria. Specifically, the study examined the impact of waste recycling and landfills on economic sustainability. The study adopted a survey research design. The population comprises the top management cadre (176) and the human resource department (22). Stratified and convenience sampling techniques and Taro Yamenes’ formula was used to determine the sample size at 132. With the aid of SPSS IBM version 25, multi-regression was used to test the hypotheses. Results obtained from the test of the formulated hypotheses revealed that waste recycling positively affects the economic sustainability of Nigerian Breweries Plc (P < 0.05; t = 3.198). The study's findings also showed that landfills positively impact the economic sustainability of Nigerian Breweries Plc (P < 0.05; t = 3.851). The study concluded that organic and inorganic waste management is strategically necessary for corporate sustainability. Waste recycling is recommended to ensure corporate sustainability, thereby reducing production costs and improving profitability.
Keywords: Waste Management; Waste Recycling; Landfills; Corporate Sustainability; Economic Sustainability